Nanostructure array assisted aggregation-based growth of a Co-MOF-74 membrane on a Ni-foam substrate for gas separation. Issue 96 (3rd October 2016) - Qin, Xi; Sun, Yuxiu; Wang, Naixin; Wei, Qi; Xie, Linhua; Xie, Yabo; Li, Jian-Rong
Abstract : A facile nanostructure assisted aggregation-based method was developed to fabricate a continuous Co-MOF-74 membrane on a Ni-foam substrate. The obtained Co-MOF-74 membrane presents good H2 /CO2 selectivity. Abstract : Metal-organic frameworks (MOFs) are promising candidates for membrane-based gas separation due to their regular crystalline lattices with relatively well-defined pore structures. To date, the preparation of integrated MOF membranes grown on porous substrates is still a major challenge. Herein, a facile aggregation-based growth method is developed to prepare a Co-MOF-74 (referred to as Co2 (dobdc), H4 dobdc = 2, 5-dihydroxyterephthalic acid) membrane on a nanostructure array modified nickel (Ni) foam substrate. Ni3 S2 nanorod arrays directly grown from the Ni-foam substrate can aggregate and effectively regulate the growth of Co-MOF-74 crystals along a given direction. The effect of reaction time on membrane growth is discussed. The resulting Co-MOF-74 membrane presents good H2 permeance and H2 /CO2 selectivity.